Taxonomic review of the rare Mexican snake genus Chersodromus (Serpentes: Dipsadidae), with the description of two new species - Canseco-Márquez, Luis; Ramírez-González, Cynthia G.; Campbell, Jonathan A. (Zootaxa, 2018)
Chersodromus is an endemic Mexican genus of snakes characterized by fused prefrontals shield. Only two species were previously known within the genus, C. liebmanni and C. rubriventris. We describe two new congeners, one from the Sierra Madre Oriental of northern Puebla and another from the Atlantic lowlands of the Chimalapas region in southeastern Oaxaca. These new species can be clearly differentiated on the basis of their morphology. Diagnostic characters distinguishing congeners include the number of dorsal scale rows, supralabials, and infralabials contacting anterior chinshields; whether or not the mental contacts the first pair of chinshields; and the coloration of the belly. We provide hemipenal descriptions of three species for which males are known.